The differences and similarities between ancient and modern furniture - Dildora Urokova Ibragimovna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract Furniture has evolved significantly over millennia, reflecting changes in materials, technology, culture, and societal needs. Ancient furniture, exemplified by Egyptian thrones, Greek klismos chairs, and Roman couches, was primarily handcrafted from natural materials like wood, ivory, and precious metals, emphasizing ornamentation, status, and durability. In contrast, modern furniture prioritizes functionality, mass production, ergonomics, and sustainability, utilizing industrial materials such as metal, plastic, and engineered wood. This article examines key similarities—such as core functional purposes (seating, storage, sleeping) and cultural symbolism—and differences in design, construction, and accessibility. Drawing from historical analyses and regional traditions, including Uzbek wood carving practices, the study highlights how ancient influences persist in contemporary design while modern innovations address contemporary lifestyles. The comparison reveals furniture as both a practical necessity and a mirror of human progress.